Coping Strategies of High-Achieving Students in Boarding Excellence High Schools: A Case Study - Zulvi, Jilsy Dzikrina; Abidin, Zainal (GoAcademica Research & Publishing, 2025)
This study aims to describe coping strategies for outstanding students in boarding high schools. The case study method was used to obtain an overview of students' coping strategies. An overview of coping strategies was obtained from three students who had the highest achievements in their class using thematic analysis. The results of the study revealed that students used various coping strategies in dealing with stressors, students used Emotion-Focused Coping to adapt to stressors and did Problem Focus Coping to overcome the problems they faced. This research reveals that with the right strategy, individuals can maintain their performance and deal with existing pressures both from within and from the environment.